Synthesis of Fe-doped Mn-based Prussian blue hierarchical architecture for high-performance sodium ion batteries. (20th April 2023) - Wang, Jie; Wang, Ziqi; Liu, He; Gao, Jiafeng; Xu, Yutong; Chen, Zui; Li, Xiaoling; Liu, Yu
Highlights: Novel Fe-doped Mn-based Prussian blue hierarchical architecture has been developed. The formation mechanism of Fe-doped Mn-based Prussian blue architecture is proposed. Fe doping sufficiently activates the redox couple reactions of the high-spin MnHS. Porous sphere-like hierarchical structure is conductive to fast capacitive behavior. Unique Prussian blue cathode shows high rate performance and good cycling stability. Abstract: Sodium manganese hexacyanoferrates (MnHCFs) have great potential as cathode for sodium-ion batteries (SIBs) owing to their large specific capacity, low cost, ecofriendly synthesis and high working voltage. Nevertheless, their cycling stability is limited by Jahn-Teller effect (JT-effect) of Mn 3+, phase transitions and Mn 2+ dissolution during the charging and discharging processes. Herein, an unconventional solid-liquid two-phase route is developed to fabricate a novel hierarchical nanostructure Na1.02 Mn0.57 Fe0.43 [F e (CN)6 ]0.63 ∙1·39H2 O in view of different solubility of raw material Na4 Fe(CN)6 ·10H2 O in the mixed solvent of ethanol and water. Benefiting from unique porous hierarchical architecture, good structural stability, high electrical conductivity and fast capacitive behavior, such Fe-doped MnHCF cathode has an outstanding rate capability with large discharging capacity of 127 mAh g −1 at 25 mA g −1 and 71 mAh g −1 at 1200 mA g −1, and an excellent cyclability with 120 mAh g −1 of specific capacity at 100 mA g −1 and 86% of capacity retention over 200 cycles. In particular, the facile and controllable synthesis process of Fe-doped MnHCFs make it accessible for large-scale applications. Graphical abstract: An unconventional solid-liquid two-phase synthetic strategy for a novel Na1.02 Mn0.57 Fe0.43 [F e (CN)6 ]0.63 ∙1·39H2 O hierarchical structure has been developed in terms of different solubility of raw material Na4 Fe(CN)6 ·10H2 O in the mixed solvent of ethanol and water. Benefiting from unique hierarchical architecture, Fe-doped Mn-based Prussian blue cathode delivers good sodium storage performance. Image, graphical abstract